A new species of Polynoncus Burmeister (Coleoptera: Trogidae) from Argentina - Costa-Silva, Vinícius; Diéguez, Víctor Manuel (Zootaxa, 2020)
Trogidae (Coleoptera) is a cosmopolitan family with about 350 described species within five extant genera (Zídek 2013, 2017; Strümpher et al. 2014, 2016; Nikolajev 2016). For South American, three genera are recorded: Trox Fabricius, 1775 (Troginae), Omorgus Erichson, 1847 (Omorginae), and Polynoncus Burmeister, 1876 (Omorginae) (Scholtz 1990; Strumpher et al. 2016; Huchet & Costa-Silva 2018).